(untitled) (FULafia Journal of Science and Technology, 2020)
This paper examines the free vibrational effect of a footbridge with compressive forces. The governing partial differential equation were analysed to determine the behaviour of the system under consideration. The methods of series solution and numerical method were used to solve the governing equation. Result revealed there is no noticeable effect of damping in the system as the motion of deflection remains constant for all values of the damping coefficient. Also, the lateral displacement increases for various values of spring constant.